2021
DOI: 10.1161/jaha.120.016617
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Mortality in Patients With Liver Cancer After Fontan Operation

Abstract: Background Liver cancer (LC) is a serious late complication after the Fontan operation. However, the incidence, predictors, and prognosis remain unknown. The purpose of our study was to determine these clinical characteristics. Methods and Results We assessed liver function in 339 consecutive patients who had undergone the Fontan procedure from 2005 to 2019. LC was histologically diagnosed in 10 patients after a median period of 2.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…After data collation, four studies were excluded to prevent duplication of data 22–25 . Of the remaining 23 studies, 12 and 13 studies were included in the cirrhosis and HCC cohorts, respectively, with two studies, Wu 2017 and Munsterman 2019, common to both cohorts 4,6–8,26–44 . The included studies in cirrhosis and HCC cohorts are reported in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After data collation, four studies were excluded to prevent duplication of data 22–25 . Of the remaining 23 studies, 12 and 13 studies were included in the cirrhosis and HCC cohorts, respectively, with two studies, Wu 2017 and Munsterman 2019, common to both cohorts 4,6–8,26–44 . The included studies in cirrhosis and HCC cohorts are reported in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5 The risk of progression of FALD to cirrhosis and subsequent risk of hepatocellular carcinoma (HCC) increases over time, regardless of type of Fontan surgery or age at Fontan. [6][7][8][9] Studies across the globe have reported variable rates of cirrhosis and HCC development, which may be secondary to multiple factors related to patient characteristics and underlying comorbidities. Given the significant morbidity and mortality associated with cirrhosis and HCC, several institutes have adopted their own protocol of routinely screening Fontan patients, often based on past experiences with other chronic liver diseases such as hepatitis C (HCV).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed pathophysiology is related to the dual blood supply of the liver, with the hepatic vein in direct continuity with the pulmonary artery, leading to increased susceptibility of hepatic parenchymal injury from decreased portal vein oxygenation and increased intrahepatic congestion, ultimately leading to ischaemic hepatitis, characterised by centrilobular necrosis around the hepatic veins. With each injury cycle, increased fibrosis and cirrhosis occurs, leading to FALD presentation 2–5 15…”
Section: Discussionmentioning
confidence: 99%
“…Elevated central venous pressure and diminished cardiac output lead to sinusoidal dilation, edema and centrilobular hepatocyte hypoxia. These changes lead to hepatic fibrosis, a common feature found in Fontan patients 3–10. As in non-FALD patients, these changes ultimately may lead to cirrhosis and hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, Ohuchi H, et al studied in 339 consecutive Fontan patients demonstrated that elevated APRI and FIB-4 scores together with older age and high plasma levels of AFP could be useful predictors of HCC in patients following Fontan operation. 13 Moreover, Egbe AC, et al reported that patients with HCC had a longer duration of post-Fontan operation along with high serum AFP levels. 5 The MRI with hepatocyte-specific HCC should be performed when the HCC feature was detected by CT scan, including enhancement during the arterial phase and wash out during portal venous phase together with elevated AFP level.…”
Section: Discussionmentioning
confidence: 99%